2012
DOI: 10.1007/s12468-012-0043-2
|View full text |Cite
|
Sign up to set email alerts
|

Individual determinants of research utilization by nurses: a systematic review update1)

Abstract: Background: Interventions that have a better than random chance of increasing nurses' use of research are important to the delivery of quality patient care. However, few reports exist of successful research utilization in nursing interventions. Systematic identification and evaluation of individual characteristics associated with and predicting research utilization may inform the development of research utilization interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(153 reference statements)
0
2
0
Order By: Relevance
“…() conclusion that education increases readiness for change and Squires et al. () finding that nurses with higher degrees have a more positive attitude towards research use, quality of care and skill enhancement. Similarly, we found that nurses with more nursing work experience have higher change commitment than those who are newer to the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() conclusion that education increases readiness for change and Squires et al. () finding that nurses with higher degrees have a more positive attitude towards research use, quality of care and skill enhancement. Similarly, we found that nurses with more nursing work experience have higher change commitment than those who are newer to the field.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to contextual and structural factors, individual factors influence readiness for change (Benzer et al., ). For example, Madsen, Miller, and John () posited that education has a positive influence on readiness for change; however, Squires, Estabrooks, Gustavsson, and Wallin's () systematic review indicated that education's impact on research use applied only to nurses with graduate degrees.…”
Section: Introductionmentioning
confidence: 99%